Interkuturelle Erziehung am Beispiel PASCH - Iwa Sobara (Allemania, 2013)
PASCH stands for the „Schulen: Partner der Zukunft“ (Schools: Partnersfor the Future) initiative. This project aims to promote German as a foreignlanguage in education, to improve relationship especially for the youngergeneration to Germany and of course to improve the knowledge of the targetlanguage country. Through the language course in Germany, the studentsfrom different countries with different backgrounds, different languagesand culture can learn from each others about everything. Thus they allowthem to have the opportunity to expand their intercultural competence aswell as their knowledge of German. The PASCH project by the GoetheInstitute allows students to acquire intercultural competence.